Chemical and Physical Properties Analysis of Carbonate Rocks from Vang Vieng, Lao PDR - Chanthala, Keositthiphone; Bounyavong, Sengthong; Singsoupho, Sounthone; Sompaserth, Sackxay; Khanthavy, Khamla; Sanlasy, khamphay; Lathdavong, Lemthong (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
The objective of this research was to analyze the chemical and physical properties of natural carbonate rocks from three distinct sampling locations in Vang Vieng District, Lao PDR. The study aimed to assess the potential of these rocks as soil amendment materials, specifically their capacity to supply essential magnesium (Mg) to acidic soils. Three individual natural rock specimens (DC1, DC2, DC3) and a commercial dolomite reference (DLM) were subjected to initial physical characterization, including hardness, density, and porosity. In addition, their chemical composition and mineral structure were analyzed using X-ray Diffraction (XRD) and X-ray Fluorescence (XRF) techniques. The XRD analysis revealed that the natural carbonate rock samples under investigation were predominantly Limestone (Calcite), exhibiting the characteristic peak of Calcite at the 2θ=29.4o position. In agreement with the XRD data, the XRF results showed a very high Calcium Oxide (CaO) content of approximately 97% and a very low Magnesium Oxide (MgO) content about 1% in samples DC1 and DC2. This conclusively confirms that these rocks are not chemically classified as Dolomite (CaMg(CO3​)2​). Sample DC3−1 also showed a trace level of Phosphate (P2​O5​) at approximately 1.17%, which serves as an auxiliary nutrient for plants. Based on these results, the carbonate rocks from Vang Vieng are suitable for use as carbonate-based amendments to increase soil pH, but they are not an sufficient source of magnesium required for effective agricultural soil improvement.